(untitled) (International journal of artificial intelligence, 2025)
This article is devoted to the principles, forms and methods of implementing educational and psychological work in educating young people in the spirit of military patriotism, in which the content, goals and objectives, main directions and forms of educational work, analysis of the state and practice of discipline, the spiritual and moral state of military personnel and the moral and spiritual climate of the team are scientifically described. This knowledge is of great importance in training mature patriotic military personnel.